2023
DOI: 10.1002/ejp.2083
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of a new episode of low‐back pain in a community inception cohort

Abstract: Background Most studies investigating the prognosis of low back pain (LBP) enrol people presenting for care, rather than all people who have an episode of LBP. We aimed to describe the prognosis of an acute episode of LBP in a community inception cohort. Methods We used data from two previous studies investigating recurrence of LBP. Participants without current LBP were contacted monthly to assess if they had experienced a new episode of LBP. 366 participants reporting a new episode of LBP were included in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…We preliminary examined a diverse sample of community-based participants to determine the transition fro acute LBP to chronic LBP at 3 and 6 months. In contrast to a recent study of community-based participants in Australia [15], we identified a relatively high incidence of chronic LBP at 3 months following a new acute episode Interestingly, the transition rates reported in this cohort are consistent with a recent study of US patients seeking ca and potentially identify a "hidden" burden of chronic LBP among community-based participants who may not see in the first 6 months of a new LBP episode. This is important because previous studies have reported as many as 42 community-based participants do not seek care for LBP [22].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We preliminary examined a diverse sample of community-based participants to determine the transition fro acute LBP to chronic LBP at 3 and 6 months. In contrast to a recent study of community-based participants in Australia [15], we identified a relatively high incidence of chronic LBP at 3 months following a new acute episode Interestingly, the transition rates reported in this cohort are consistent with a recent study of US patients seeking ca and potentially identify a "hidden" burden of chronic LBP among community-based participants who may not see in the first 6 months of a new LBP episode. This is important because previous studies have reported as many as 42 community-based participants do not seek care for LBP [22].…”
Section: Discussionsupporting
confidence: 81%
“…For example, a recent Australian community-based cohort study indicated that acute LBP’s prognosis is far better than in clinical populations. [15] However, the same may not be accurate in the US, given the differences between these countries (e.g., demographic makeup, sociopolitical, and healthcare characteristics). The limited US community-based studies also indicate that chronic LBP incidence is higher than previously thought (approximately 25%).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are consistent with similar work. In a community cohort, De Campos and colleagues 131 found that a subsequent new episode of acute low back pain resolved rapidly (about 5 d) among participants who had recently recovered from low back pain (including participants enrolled in a randomized controlled trial to prevent recurrence of low back pain). A systematic review of randomized controlled trials reported a similar pattern of improvement within the first 6 weeks and less pronounced improvement at longer-term follow-up (1 yr).…”
Section: Discussionmentioning
confidence: 99%
“…So Tarcisio F. de Campos, from Macquarie University, and a group of Australian and Brazilian researchers decided to perform an inception cohort study of a community-dwelling population—of people who did not have back pain and were not seeking care at the beginning of the study. (See de Campos et al, 2023. )…”
Section: A Study Of Back Pain In the Communitymentioning
confidence: 99%